Bean mutant induced by ionizing radiation. II. Yellow mosaic mutant - Moh, C.C.; Alan, J.J. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Through the irradiation of common bean (Phaseolus vulgaris L.) seeds of the S-182N variety with an acute dose of gamma radiation from a cobalt-60 source, a mutant called yellow mosaic was induced in the R generation. This mutant was isolated in subsequent tests of its progeny. This mutant exhibits yellow mottling on the primary and compound leaves, the appearance of which is very similar to the symptoms caused by yellow mosaic disease of beans. This mutant does not produce flowers and is therefore sterile. Genetic studies revealed that the mutant is a recessive trait that occurs in a simple Mendelian ratio. There was no difference in seed production between normal homozygous plants and beta-zygous plants.